THE PROBLEM OF CYBERBULLYING IN THE DIGITALIZATION ERA WHICH HAS A NEGATIVE IMPACT ON PUBLIC LIFE - Lewika Tampubolon; Zailani Sinabariba; Norita Tampubolon; Penggabean Siahaan; Muhammad Amin (RADJA PUBLIKA, 2025)
In the era of rapidly developing information and communication technology, social interactions have shifted significantly to digital platforms. While this progress brings many benefits, such as ease of communication and access to information, information technology can also have significant negative impacts, one of which is the emergence of cyberbullying. Cyberbullying is behavior intended to humiliate, intimidate, injure, or cause harm to a vulnerable party using information technology communication tools. In other countries, there are many cases of cyberbullying that end in more serious incidents such as suicide. This paper uses a qualitative method with a literature review approach. This approach was chosen to in-depth explore various literature and previous research related to the topic of bullying among the community, especially teenagers in the digital era. The results of the study indicate that the negative impact of information technology on cyberbullying cases has occurred at a fairly large rate (28%), but the impact is not very serious. From the answers given, it can be concluded that many people do not understand cyberbullying and its potential impacts. This study also explores the roles, responsibilities, and actions of teenagers, parents, schools, and law enforcement.